Pengambilan keputusan seorang istri dalam pernikahan poligami - Rahmawati, Sri W. (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2013)
Polygamy marriage is a social reality that occurs in our community, which responded with a variety of responses. Dynamics of wedding process is something unique. This paper is a qualitative study of decision making process in women who undergo a polygamous marriage, during the marriage enters the age of 11 years. Decision making is intended to obtain the expected results and avoids conlict. A qualitative design is performed because this approach gives a deeper interpretation of human behavior which quantiied dificulty. Decision making is not a simple process, because there are many considerations inluenced by subjective factors, such as the preference value, as well as environmental factors.